Ciclo reprodutivo, gametogênese e desenvolvimento larval de Asterina stellifera (Möbius, 1859) (Echinodermata: Asteroidea) na região de Cabo Frio, RJ - Carvalho, Adriana Luiza Pimenta Sant'Iago de (2001)
The development and reproductive cycle of Asterina stellifera were studied from amples taken from populations in two distinct habitats from Cabo Frio. One is an intertidal seagrass flat at Japonês lsland ( 1994-1995); the second is a sublittoral rocky-shore at Pontal Beaches ( 1999-2000). Development pattern was described based on laboratory cultures. Reproductive cycle was studied at monthly intervals by organ indices and histological examinations of gonads. A. stellifera has a typical planktotrophic development with bipinnaria and brachiolaria stages. The periodicity of the annual reproductive cycle was similar for both populations, but the gonad índex (Gl) was higher and the pyloric caeca index (PCI) had less variation in the rocky-shore population. The Gl and PCI had an inverse relationship in both populations, but it was greater in the seagrass-flat population. Environmental factors like hydrodynamics and food availability are the most probable mechanisms for these differences.